Successful nonsurgical management of pelvic organ prolapse in infertility: a case series - Pandey, Mily; Pandey, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Pelvic organ prolapse is a less commonly cited cause of female factor infertility. This could be attributed to cervical factor or to distorted utero tubal relationship. When the cervix constantly lies outside the vagina, there is impaired venous return resulting in congestion, inflammation and ulceration, which is further aggravated by friction. Cervical dryness even hampers sperm and cervical mucus interaction leading to impaired capacitation. Here, we present 4 cases of cervico vaginal descent where main presenting complain was inability to conceive and were diagnosed to have prolapse on clinical workup. These cases had successful pregnancy outcome after conservative management with the placement of vaginal ring pessary of appropriate size. This reposits the cervix inside vagina, reduces cervical oedema, dryness and restores cervical mucus formation.